Voices of Teens and Young Adults on the Subject of Teleconsultation in the COVID-19 Context. (April 2022) - Ziani, Melissa; Trépanier, Emmanuelle; Goyette, Martin
This article describes the perceptions of adolescents and young adults aged 14 to 25 years who live in Québec (Canada) and obtained health services via teleconsultation for the first time, owing to the COVID-19 pandemic. Eleven young people who had received physical health services (medicine, physiotherapy, speech therapy, or nutritionist) participated in virtual semi-structured interviews. These interviews shed light on how these adolescents and young adults experienced the adaptation of the intervention and how effective they perceived the intervention to be. The article concludes with some thoughts for practitioners.